1987
DOI: 10.1007/bf01541421
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of sexual contact of boys with women

Abstract: The incidence of sexual contact with boys by women was found more prevalent than had been contended in the clinical literature. Male penitentiary inmates reported higher heterosexual contact as children than did college men. The effects upon the boy and his later adult sex life were generally reported as not traumatic, although coercion by the woman tended to be associated with a bad feeling about the experience at the time and a negative effect upon adult sex life. The majority of women were friends, neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
6

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 12 publications
3
46
0
6
Order By: Relevance
“…As an example, for neutral reactions, they claimed that we coded Condy et al's (1987) "mixed" category and Long and Jackson's (1993) "low" and "ambivalent" responders as neutral reactions, yet nowhere did we reveal this to our readers. This claim is simply false; in Table 7 (Rind et al, 1998, p. 36), we used superscript a for our neutral percents for both of these studies, clarifying the coding procedure.…”
Section: Additional Criticisms By the Leadership Councilmentioning
confidence: 87%
See 1 more Smart Citation
“…As an example, for neutral reactions, they claimed that we coded Condy et al's (1987) "mixed" category and Long and Jackson's (1993) "low" and "ambivalent" responders as neutral reactions, yet nowhere did we reveal this to our readers. This claim is simply false; in Table 7 (Rind et al, 1998, p. 36), we used superscript a for our neutral percents for both of these studies, clarifying the coding procedure.…”
Section: Additional Criticisms By the Leadership Councilmentioning
confidence: 87%
“…In our review, we first examined self-reported negative effects on subjects' current sex lives or attitudes. For males, negative effects ranged from 0.4 percent (Landis, 1956) to 16 percent (Condy et al, 1987). We computed their unweighted mean, obtaining 8.5 percent.…”
Section: The Leadership Council and Its Criticism That We "Loaded Ourmentioning
confidence: 99%
“…As noted previously, researchers have generally found either no effects on psychological adjustment or only small effects on a minority of the measures. Furthermore, researchers using college students to measure reactions to these experiences have shown that they are variable, ranging from negative to positive, with about two thirds of men and one third of women on average reacting in a neutral or positive way (Condy, Templer, Brown, & Veaco, 1987;Finkelhor, 1979;Fromuth & Burkhart, 1987;Goldman & Goldman, 1988;Landis, 1956;Li, West, & Woodhouse, 1993;O'Neill, 1990;Schultz & Jones, 1983;Urquiza, 1988). Positive short-term reactions in the nine studies just cited ranged from 6% to 69% for males (M = 39%) and from 2% to 28% for females (M = 14%), indicating a sizable sex difference.…”
Section: Review Of the Psychological Correlates Of Adult-nonadult Sexmentioning
confidence: 96%
“…criminal settings (Burgess, 1988;Petrovich, 1984;Groth, 1979Groth, , 1986, educational settings (Condy, 1987;Hibbard, 1990), hospital settings (Dube, 1988;Hunter, 1987;Reinhart, 1987), and adult and child clinical samples (Bentovim, 1987;Carmen, 1984;Faller, 1989;McCormack, 1986).…”
mentioning
confidence: 99%
“…Lower socioeconomic status, regardless of race, is also associated with increased risk of victimization (Condy, 1987;Faller, 1989).…”
mentioning
confidence: 99%